Adversity Quotient Among Students in a Professional Psychology Education Program: A Phenomenological Study - Qudzam Rizqisailu; Ahmad Adin Sutariyono; Mathayo Marko Nassari; Sri Lestari (Journal An-Nafs: Kajian Penelitian Psikologi, 2026)
Although adversity quotient (AQ) has been widely examined in relation to academic resilience and stress among university students, little is known about how AQ is experienced by students in professional psychology education, who face intensive academic, emotional, and practicum-related demands. This study therefore aimed to explore the lived experiences of AQ among students in the Professional Psychology Education Program at University X. A qualitative phenomenological design was employed, and data were collected through semi-structured interviews with three students selected using purposive sampling. The interview data were analyzed using thematic analysis to identify patterns underlying participants' experiences of coping with professional education challenges. The findings revealed six major themes that characterize students' AQ. Four themes—Control, Origin and Ownership, Reach, and Endurance—correspond  to Stoltz's AQ framework and describe students' abilities to regulate themselves, assume responsibility for difficulties, limit the impact of adversity, and persist through academic and practicum challenges. More importantly, the study identified two additional themes, namely social support and spirituality, which emerged as essential contextual resources that strengthen students' resilience throughout their professional education. These findings suggest that students' AQ is shaped not only by individual psychological capacities but also by supportive interpersonal relationships and spiritual meaning-making processes. Conceptually, this study suggests that the existing AQ framework may be enriched by considering the role of contextual resources within the professional psychology education setting, where resilience is shaped through dynamic interactions among personal, social, and transcendental factors. The findings provide a richer contextual understanding of AQ and offer practical implications for designing professional education environments that foster psychological resilience through academic support, social connectedness, and spiritual well-being.